2021
DOI: 10.31248/jasvm2021.249
|View full text |Cite
|
Sign up to set email alerts
|

In vitro oocysticidal sporulation inhibition of Eimeria tenella and antioxidant efficacy of ethanolic and aqueous extracts of Conyza aegyptiaca

Abstract: Avian coccidiosis is probably one of the most expensive parasitic diseases with major economic impact on poultry industries worldwide. The purpose of this study was to evaluate the ethanolic and aqueous extracts of Conyza aegyptiaca in terms of phytonutrients, in vitro oocysts sporulation inhibition and antioxidant properties. The extraction process of plant leaf powder (100 g) pulverized using a clean manual grinder was carried out in ethanol and hot water and the yields were calculated as a percentage ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Several investigators found that rosemary bioactive properties are connected with the presence of phenolic compounds, especially flavonoids and diterpenes, such as carnosic acid and carnosol that characterized with its antioxidant activity [76][77][78]. These researchers further reported that extracts containing polyphenolic compounds may have the ability to inhibit enzymes responsible for the sporulation process of the coccidian oocysts [79]. Additionally, in the current study, the highest concentration (10 mg/ml) of UEERO showed the highest percentage in sporocysts abnormalities with the highest distortion (%) in oocyst wall, while the lowest concentration (0.01 mg/ml) exhibited the lowest sporocysts abnormalities (%) with the lowest distortion (%) in oocyst wall.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators found that rosemary bioactive properties are connected with the presence of phenolic compounds, especially flavonoids and diterpenes, such as carnosic acid and carnosol that characterized with its antioxidant activity [76][77][78]. These researchers further reported that extracts containing polyphenolic compounds may have the ability to inhibit enzymes responsible for the sporulation process of the coccidian oocysts [79]. Additionally, in the current study, the highest concentration (10 mg/ml) of UEERO showed the highest percentage in sporocysts abnormalities with the highest distortion (%) in oocyst wall, while the lowest concentration (0.01 mg/ml) exhibited the lowest sporocysts abnormalities (%) with the lowest distortion (%) in oocyst wall.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids can also penetrate the cell membranes and cause sporozoite and oocyst death ( 171 , 242 ). Multiple plants, such as, Moringa oliefera and Syzygium aromaticum , with active flavonoids have anticoccidial activity ( 170 , 188 , 240 , 243 245 ).…”
Section: Methodsmentioning
confidence: 99%